Deeds not words: Performance and management analysis of community water supply system at Pasthali, Kavre, Nepal - Dongol, R.; Khadka, M.; Kharel, R.P. (Nepal Journal of Environmental Science, 2016)
The study was carried out to assess the performance and management analysis of Pasthali Water Supply System. Various data collection tools such as questionnaire survey, field observation and key informant interviews were used along with water quality analysis at the source, treatment plants, point of delivery and use. The filter bed media analysis was also carried out to assess the uniformity in the bed media. Mcrobial contamination in treated water was found due to improper sand granular used in filtration unit that hinder efficient removal of the microbes, lack of chlorination in the unit caused increase in microbial contamination at the point of delivery along with the unhygienic environment at the distribution tanks. Manual chlorine addition for three days was found to be effective in reducing microbial contamination drastically, but the water is recontaminated once delivered and stored at the household level. Improper handling and unhygienic storage location were found to be the major causes of increased contamination at households. The status of the water source is not safe either and seeks intermediate attention. The operation and management of Pasthali Water Supply System solely depends on water tariff and bears financial loss annually. The study also concludes that there is surplus of treated water termed as non-revenue water in the system. Proper granulation of the sand in the filtration unit and chlorination are must to ensure the safe water along with the awareness on the water management at the household levels. Supplying of non-revenue water to the nearby villages could be a potential to generate resources that ultimately strengthen financial aspects of the system and build resilience to financially break-down in the future.